A revised capacitance resistance model for large diameter shallow bore ground heat exchanger. (5th November 2019) - Najib, Antash; Zarrella, Angelo; Narayanan, Vinod; Grant, Peter; Harrington, Curtis
Highlights: The thermal performance of shallow helical ground heat exchangers is investigated. A lumped parameter model CaRM and a commercially CFD software are used. The CaRM tool is improved to better model the heat transfer inside the borehole. The results of the revised CaRM tool match better with CFD outcomes. The CaRM tool is an attractive solution to decrease the computational time. Abstract: Ground heat exchangers (GHE) for residential heat pumps have the advantage of rejecting (extracting) heat to a lower (higher) temperature sink (source) as compared with air source heat pumps. The thermal performance of shallow GHEs with larger diameter and of helical shape is modelled in this study using both a lumped parameter numerical model and a commercially available computational fluid dynamics (CFD) software. Measurements in a real test site single-family residence are also used for soil property calibration. The lumped parameter numerical model (Capacitance Resistance Model, CaRM) is validated against the CFD simulation results and improved in order to capture detailed heat transfer processes within the core of the GHE. As result, the new CaRM model is able to better simulate the thermal behaviour of the helical GHE without high computational resources of the CFD model. Detailed local and global temperatures predicted by the numerical models are presented and discussed. Results indicate that the new CaRM tool better matches the trend of the CFD model. The average root-mean-square deviation between the revised CaRM and CFD models are 0.29 °C for the average core temperature and 0.75 °C for the borewall temperature which is an improvement of 27% and 35% respectively, in comparison to the previous version of CaRM.